Paleobioindicators from the world’s end: Ostracods and chironomids from Quaternary lacustrine environments of the southern tip of South American (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The main goal of this contribution is to summarize our current knowledge on paleolimnological research in Argentina using bioproxies, particularly ostracods (Crustacea) and chironomids (Diptera). Additionally, we present our perspective on the strengths and weaknesses of the major approaches to reconstruct past climate from these biological proxies. Ostracod and chironomid assemblages are powerful tools in Paleolimnology. These arthropods live in conti- nental waters where they can reflect climate and environmental changes because of their high sen- sitivity to variations in the physical and chemical parameters controlling aquatic systems. Based on their modern ecological requirements it is possible to apply numerical, multivariate, and qualitative techniques to reconstruct some key parameters of late Quaternary environments.For the past 20 years, the use of modern and fossil ostracods and chironomids has increased significantly allowing the development of robust and unbiased high-resolution environmental recons- tructions including climate applying multivariate approaches (i.e., transfer functions) and qualitative interpretations. Indicator species often consolidate investigations. The combination of biological, physical, and chemical proxies provides a network of independent data that allow the comprehensive understanding of late Quaternary continental aquatic ecosystems. Ostracods and chironomids have permitted not only to recognize long- and mid- term climate and environmental trends but also high frequency climatic events of global interest, like the Younger Dryas (YD), the Antarctic Cold Reversal (ACR), the “4,2ka Dry Event”, and the Little Ice Age (LIA), as well as climate changes occurred during the 20th century, including anthropogenic impact. Most of these studies have been performed in North America and southern Patagonia of Argentina, permitting to reconstruct the climatic and environmental evolution since the Last Glacial Maximum (LGM). More recently, this kind of research has expanded towards lower latitudes in Argentina, like the Pampas Plain and the Northwest Argentine Altiplano or Puna, covering different temporal windows of the middle and late Holocene (Fig. 1).To date, Patagonia offers the best records due to the active research conducted by local and foreign scientist. Based on the suitability of high-resolution sedimentary archives (Table 1), these studies have proven useful for understanding the evolution of the Southern Hemisphere Quaternary climate. This is especially true for the Andean lakes that may include continuous sequences since the LGM. (Whatley and Cusminsky, 1995, 1999; Cusminsky and Whatley, 2008; Cusminsky et al., 2011; Massaferro et al., 2004, 2009, 2014). By contrast, the Patagonian steppe lakes and ponds may be more sensitive to environmental change but the records are shorter, younger, and fragmentary (Massaferro and Laroque, 2013; Ramón Mercau et al., 2010, 2012b). In spite of the good quality of records in Patagonia, the vastness of the region, and the unattainability of some areas, it makes sometimes difficult to assess the systematic position and autoecology of the taxa involved at the expense of the reconstruction’s quality. On the other hand, the Pampean records (Fig. 1, Table 2) include mostly Holocene sediments allowing the understanding of the trophic history (Laprida et al., 2014), rainfall patterns (Laprida and Valero Garcés, 2009) and climate gradients (Laprida et al., 2009) in one of the most social-economically important regions of the country.The results obtained in this study corroborate the potential value of these arthropods as proxies of late Quaternary environmental change, and suggest directions of future research to improve our understanding of the biological interactions with the environment and climate. New investigations are required on the taxonomy of modern ostracods and chironomids, their ecological requirements and distribution to be able to extrapolate this know- ledge to the past generating calibration methods that would cover broad gradients. The development of quantitative techniques for inferring past environments from paleoecological data and of mul- tiproxy studies using several variables, can allow the study of biotic responses to and the testing of hypotheses about climate change.
Keywords: Ostracods, Chironomids, Paleolimnology, Late Quaternary, Argentina.